10–8 Foundation year simulation (FYSIM): feedback from course pilot and barriers to participation. (17th November 2017) - Newton, JC; McGrory, GM; Paton, C
Abstract : Introduction: Simulation provides an effective means of delivering medical education within a safe learning environment, and it is increasingly included within postgraduate training programmes. We have developed a new medical simulation course for doctors at the end of Foundation Year 1 (FY1) in response to local demand. We have collected feedback from FY1 attendees at our pilot course and investigated barriers limiting attendance. Methods: We have designed a simulation course (FYSim) based around the management of medical emergencies to assist FY1 doctors in achieving their learning outcomes as specified in the foundation curriculum, and to prepare them for their second foundation year (FY2). We collected written questionnaires from attendees at our pilot course in June 2016. As attendance was limited, we collected data on barriers to participation amongst the FY1 cohort. Results: One course participant described FYSim as being 'very useful in getting more practice of tricky scenarios before we begin FY2' and felt they particularly developed their ability to manage tachyarrythmias, major haemmorrhages and seizures. Attendees rated the course between 4/5 and 5/5 on Likert scales in helping them develop a range of non-technical skills. In summary, one participant describes a 'superb course' and that 'all should come' in order to best prepare for FY2. We had 26 responses to the barriers questionnaire from a total cohort of 67 FY1s. The major barriers listed were in relation to service pressures and not having formal study leave: Motivation was an issue, one FY1 describing themselves as 'tired/jaded from unfulfilling ward work'. However, others regretted not being able to attend, stating 'I would have loved the opportunity to do this'. Conclusion: We have received positive feedback from our pilot course from FY1s who feel it fulfils its role of increasing preparation for FY2. A larger study will help to confirm this, and we have identified a range of barriers limiting attendance. These will be discussed within the medical education department to design a strategy to maximise attendance in the following year.